Experimental study on the influence of liquid reservoir on the performance of two-phase thermosyphon loop - Jia Yang; Yan Xie; Xiaorui Yang; Zhihua Zhang; Jiabei Zhong; Penglei Zhang (Case Studies in Thermal Engineering)
Two-phase thermosyphon loops (TPTLs) are widely used in natural cooling systems for data centers. A TPTL often includes a liquid reservoir, but the effect of this liquid reservoir on its performance has not been thoroughly explored. In this study, an experimental TPTL platform incorporating a visual liquid reservoir was established, and the flow and heat transfer performance of the TPTL, both with and without the liquid reservoir, was experimentally investigated under varying temperature differences, refrigerant charges, and installation heights for the liquid reservoir. The results showed that for a TPTL without a liquid reservoir, the height of the liquid column in the downcomer, which provided the driving force for circulation, increased proportionally with the temperature difference, reflecting the self-regulating capability of the TPTL. In contrast, for a TPTL with a liquid reservoir, the liquid column height was essentially fixed at the height of the liquid reservoir, thereby disrupting the self-regulating capability of the system. Consequently, under a large temperature difference, the system became prone to overheating (significant evaporating thermal resistance Re), due to an insufficient flow rate resulting from a limited liquid column height. Hence, the larger the temperature difference, the higher the required installation height of the liquid reservoir. In addition, the liquid reservoir accommodated the excess refrigerant, and prevented the phenomenon of liquid flooding inside the condenser, thus reducing the degree of subcooling at the outlet of the condenser and the condensing thermal resistance Rc, and expanding the optimal range of refrigerant charge. This positive effect is insignificantly related to the installation height of the liquid reservoir.